Participatory Governance in the Europe of Cross-Border Regions. Cooperation – Boundaries – Civil Society. - Ulrich, Peter (Nomos, 2021)
Die Studie untersucht geopolitische und soziokulturelle Grenzziehungsprozesse im "Europa der Grenzregionen" und den Einfluss auf zivilgesellschaftliche Partizipation und Governance in nationalen Peripherien. Mit einer ausgeprägteren bürgerschaftlichen Beteiligung an euroregionalen Institutionen und Politik wird die normative Hoffnung einer Demokratisierung und Legitimation europäischer Politik in EU-Grenzregionen verknüpft. Am Beispiel der EU-Rechtsform des Europäischen Verbunds für territoriale Zusammenarbeit werden die euroregionalen Institutionen Europaregion Tirol-Südtirol-Trentino, Galizien-Nordportugal, Eurodistrikt SaarMoselle und TransOderana tiefgründig analysiert und miteinander verglichen.

This policy analysis examines geopolitical and sociocultural bordering practices in Europe’s cross-border regions and their impact on civil society participation and governance in state peripheries. The normative hope of democratisation and the legitimisation of European politics in European Union border regions are connected with a greater degree of cross-border citizen engagement in Euroregional institutions and politics. Using the example of the European Grouping of Territorial Cooperation, this study analyses and compares four cross-border Euroregional case studies: Tyrol–South Tyrol–Trentino, Galicia–North Portugal, SaarMoselle and the planned German–Polish TransOderana EGTC.
Keywords: Grenzüberschreitende Zusammenarbeit; Regional Governance; Governance; Grenzgebiet; Periphere Region; Kooperation; Zivilgesellschaft; Bürgerbeteiligung; Euroregion; Eu-Politik; Fallstudie; Internationaler Vergleich